Karakteristik Sifat Mekanik dan Struktur Mikro Baja Laterit Paduan Ni-Cr-Mn Hasil Tempa Panas Dengan Variasi Beban Tempa [Mechanical Properties and Microstructure Characterization of Ni-Cr-Mn Alloys Lateritic Steel as a Result of Hot Forging with Variated - Satrio Herbirowo; Bintang Adjiantoro; Fatayalkadri Citrawati (Metalurgi, 2018)
NiCrMn alloy lateritic steel has a potential as an alternative for steel raw material that has high toughness and substitute the commercial AISI 4340 steel. This research is conducted to know the characteristics of lateritic steels according to AISI 4340 standard from chemical composition, mechanical properties, and microstructure after hot forging process with variety of loads and oil as cooling media. The hot forging process was carried out at temperature of 1200 °C using 3 variety of forging loads: 50, 75, and 100 tons. The forged NiCrMn alloy lateritic steel was characterized by chemical composition analysis with OES (optical emission spectrometer), metallographic observation using OM (optical microscopy), Charpy impact test, and hardness Rockwell C. The result of chemical composition analysis showed that NiCrMn alloy lateritic steel had chemical composition in accordance to AISI 4340 with modification of Ni, Cr, and Mn elements equal to (wt.%) 1.8; 1.71; 1.87. The characteristics of NiCrMn alloy lateritic steel showed that the hardness and toughness increased when the % reduction improved. In reduction percentage of 31.02% it was obtained hardness value and energy absorb equal to 61.21 HRC and 0.166 J/mm2, with structure formed was martensit phase. However, at a higher reduction percentage of 31.72%, the hardness and impact strength values decreased to 58.56 HRC and 0.19 J/mm2. This occured because of the structure formed in the NiCrMn alloy lateritic steel was a martensite phase with retained austenite. AbstrakBaja laterit merupakan baja berbahan dasar bijih nikel laterit. Bijih nikel laterit biasa diabaikan penambang karena faktor ekonomis dan lebih mencari nikel yang berada dibawah lapisan limonit. Tujuan penelitian ini adalah mengetahui karakteristik baja laterit yaitu sifat kekerasan, ketangguhan, struktur mikro, dan struktur patahan baja laterit dengan variasi beban pada proses penempaan panas (hot forging). Penempaan panas menggunakan 3 variasi beban tempa yaitu 50, 75, dan 100 ton serta bahan awal (As Cast) dengan 1 kali penempaan pada temperatur pemanasan 1200°C. Penempaan panas menghasilkan reduksi As Cast (0%), 50 ton (18.06%), 75 ton (31.02%), dan 100 ton (31.72%). Hasil pengujian karakterisasi material menunjukkan bahwa nilai kekerasan tertinggi dan nilai impak tertinggi pada reduksi 31.02% sebesar 61.21 HRC dan 0.21 Joule/mm2. Struktur mikro yang terbentuk pada As Cast adalah ferit dan perlit sedangkan pada hasil penempaan panas adalah bainit. Hasil struktur patahan menggunakan Scanning Electron Microscope menunjukkan bahwa ukuran butir semakin halus dan pipih seiring bertambahnya beban tempa panas.